Modern Approaches to Educational Process Organization: Integration of Dual Education and Innovative Technologies - Khdojaev, Nosir (MMIT Proceedings, 2025)
<article class="text-token-text-primary w-full focus:outline-none [--shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(--shadow-height) has-data-writing-block:pt-(--shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(--header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-68ebddb8-0420-832f-9ac0-c510bd5cc686-28" data-testid="conversation-turn-190" data-scroll-anchor="true" data-turn="assistant"> <div class="[--thread-content-max-width:40rem] thread-lg:[--thread-content-max-width:48rem] mx-auto max-w-(--thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="88fca271-06ac-4f38-b1d4-35dee8243546" data-message-model-slug="gpt-5"> This article examines contemporary trends in the development of higher education in the context of digital transformation and evolving labor market demands, analyzing the effectiveness of integrating the dual education system with innovative pedagogical technologies. It explores the mechanisms of tripartite partnership between higher education institutions, manufacturing organizations, and students, and presents the results of implementing modern digital solutions into the educational process and their impact on the quality of graduate training.